A deletion map of the human Y chromosome based on DNA hybridization. - Vergnaud, G (1986)
The genomes of 27 individuals (19 XX males, two XX hermaphrodites, and six persons with microscopically detectable anomalies of the Y chromosome) were analyzed by hybridization for the presence or absence of 23 Y-specific DNA restriction fragments. Y-specific DNA was detected in 12 of the XX males and in all six individuals with microscopic anomalies. The results are consistent with each of these individuals carrying a single contiguous portion of the Y chromosome; that is, the results suggest a deletion map of the Y chromosome, in which each of the 23 Y-specific restriction fragments tested can be assigned to one of seven intervals. We have established the polarity of this map with respect to the long and short arms of the Y chromosome. On the short arm, there is a large cluster of sequences homologous to the X chromosome. The testis determinant(s) map to one of the intervals on the short arm.